PENGEMBANGAN LEMBAR KERJA SISWA (LKS) NON-EKSPERIMEN HUKUM GRAVITASI NEWTON - Djoko '; Fakhruddin '; M. Sahal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to develop non-experimental student worksheet in Newtonian gravity. This research was conducted starting from May until June 2017. It is reasearch and development classification using ADDIE model without the implementation level. The subject was Newtonian gravity in the 10th grade, 2nd semester, senior high school physics subject. The research was conducted by analyzing the curriculum of physics subject in senior high school associated with Newtonian gravity, mapping the student worksheet assignment which fits to the curriculum, and the worksheet which was arranged and developed based on the planning above. The prototype of the worksheet was produced and then validated by the experts such as three physics lecturers and two physics senior high school teachers. The aspect of validation which has been assessed was the feasibility of presentment, content, and languange. After gaining the feedback from the experts, the worksheet was then edited, revised, and validated. The result of this research was analysed descriptively. According to the data, it can be concluded that the student worksheet which has been developed entirely has been catagorized as 'very high' and 'valid'. The result of validation from presentmen feasibility respectively was 3.59; 3.67; 3.75; 3.70, the content feasibility showed, 3.64; 3.65; 3.65; 3.63 , and the languange feasibility was gained in the number of 3.62; 3.62; 3.54, and 3.40.Keywords: development, non-experimental student worksheet, Newtonian gravity